The adjustment journey: writing challenges and self-efficacy of students in transition from high school to an English medium instruction (EMI) university programme in Japan - Hadingham, O (2022)

(untitled)
Research into language-related challenges confronting EMI students is accumulating but gaps in understanding remain. One skill – academic writing – has not received the close-grained attention it merits given the centrality of the essay as a means of assessing EMI students. There is also a dire need for longitudinal insights into the EMI transition and a richer exploration of its lived reality. Such research may also provide valuable pointers to improving this crucial adjustment period.